P559 Real-life experience with long-term maintenance of golimumab in ulcerative colitis patients. (25th January 2019) - Iborra, M; García-Morales, N; Rubio, S; Nantes Castillejo, O; Bertoletti, F; García-Planella, E; Calvo, M; Vera, I; Taxonera, C; Alba, C; Boscá-Watts, M; Martí-Aguado, D; et al.
Abstract: Background: PURSUIT trial demonstrated the long-term efficacy of golimumab (GLM) in ulcerative colitis (UC). However, the long-term maintenance and safety of GLM in clinical practice has not been evaluated. Methods: The aim is to assess the probability of maintenance of GLM in UC in real-life and the possible factors associated to long-term maintenance. This multi-centre cohort study included consecutive patients with moderate-to-severe UC treated with golimumab induction doses and who had at least 12 months of follow-up. We recorded baseline demographics including prior or concomitant use of inmunosupressors (IS) or steroids (CE), prior exposure to anti-TNF, and reason of withdrawal of last anti-TNF. During follow-up we evaluated the cumulative probability of maintaining GLM, and the rates of hospitalisations, surgeries and adverse events (AE). Cox regression models were used to identify predictors of GLM discontinuation. Results: A total of 193 patients were analysed (102 male (53%), 8 proctitis (4%), 75 (39%) left-sided UC and 110 (57%) extensive UC). Of all, 101 (53%) were anti-TNF naïve and 51 (27%) and 38 (20%) had previously received 1 and ≥2 anti-TNFs, respectively. The preceding anti-TNF was discontinued due to primary failure, secondary failure, AE, or other causes in 29%, 53%, 13% and 5% of patients, respectively. At baseline 187 patients (98%) received GLM induction doses of 200–100–100/50 mg at weeks 0-2-6. Subsequently, 101 patients (53%) and 87 patients (46%) started maintenance with 50 or 100 mg golimumab doses every 4 weeks, respectively. After a median follow-up of 43 months (IQR 11–66), GLM was discontinued in 108 (56%) patients due to primary failure in 63 (58%), secondary failure in 34 (32%) and AE in 11 (10%) patients. Eighty-two (43%) patients needed dose escalation during follow-up (median 20 months, (IQR 6–25). During follow-up 31 patients (16%) referred AE, 32 (16.5%) needed hospitalisation and 11 (6%) surgery. The survival probability of maintenance of GLM during follow-up is shown in Figure 1. Multi-variate analysis retained shorter disease duration as a predictor of maintenance with GLM ( p = 0.008). The number of previous anti-TNF drugs or the cause of withdrawal of these, the concomitant use of IS, and the disease extension were not associated with GLM maintenance. Conclusions: After a median follow-up of 43 months 40% of patients with refractory UC patients maintained GLM. Shorter disease duration was predictive of persistence with GLM. Long-term GLM therapy was safe and achieved low rates of hospitalisations and surgeries.